2016
DOI: 10.1007/s00289-016-1667-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of PTB7:C70 bulk heterojunction photocell prepared with halogen-free solvent at low light illumination

Abstract: Increasing social demands for clean and cheap renewable energy sources have been promoting the researches on polymer photocells based on bulk heterojunction composites consisting of conjugated polymers and fullerenes. The replacement of traditional chloroaromatic solvents such as chlorobenzene with a halogen-free solvent 1,2,4-trimethylbenzene (TMB), which enables the preparation of bulk heterojunction composites with unmodified fullerenes, potentially reduces the economic and environmental costs of organic bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…]thienophenediyl] (PTB7) as the absorber combined with [6,6] -phenyl C70 butyric acid methyl ester (PC 70 BM) as an electron acceptor for conventional configuration devices [4,5]. Recently, inverted structured OSCs with electron accepting fullerene and the electron donating polymer as the active layer have drawn great interest because of the inherent device stability and enhanced performance [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…]thienophenediyl] (PTB7) as the absorber combined with [6,6] -phenyl C70 butyric acid methyl ester (PC 70 BM) as an electron acceptor for conventional configuration devices [4,5]. Recently, inverted structured OSCs with electron accepting fullerene and the electron donating polymer as the active layer have drawn great interest because of the inherent device stability and enhanced performance [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, the characterization, as well as the development of suitable circuit model of a photocell under low‐light illumination, is essential. Recent studies have shown that polymer photocells are promising for indoor light harvesting .…”
Section: Introductionmentioning
confidence: 99%